Industrial training report: Heitech Padu Berhad / Mohammad Afiq Mohamed Sopiee - Mohamed Sopiee, Mohammad Afiq (Perpustakaan Tengku Anis, 2017)
Starting from period of 2nd February 2017 to 30th June 2017 in HeiTech Academy at HeiTech Padu Berhad, Early Takers System implementation has been proposed for the staff of HeiTech Academy. An enhancement was made by merging from Microsoft Excel format into automated system. A simple database was made to ease user to capture the data and store them on the go throughout the Early Takers project period. Early Takers System is an automated recordkeeping system which consists of several functions such as data entry, data deletion, data alteration and data searching. Purpose of the system developed is to secure data, user-friendly system, aiding the staff for data management. Data management is crucial for the on-going progress and for this industry it is crucial for the client data management.